PENGARUH ENTERTAINMENT, CUSTOMIZATION, INTERACTION, WORD OF MOUTH, DAN TREND TERHADAP CONSUMER PURCHASE BEHAVIOUR PADA SOSIAL MEDIA INSTAGRAM - Retno Rahayu; Sri Vandayuli Riorini (Bussman Journal : Indonesian Journal of Business and Management, 2023)
Behavior is a real human action that can be observed directly. While consumers are people who participate in buying or using a product. Therefore, consumer purchasing behavior is a decisionmaking method used to evaluate, obtain, use, or regulate goods and services. This research was conducted with the aim of examining and analyzing the influence of Entertainment, Customization, Interaction, Word of Mouth, and Trends on Consumer Purchase Behavior on Instagram SocialMedia. This research is a qualitative approach. Sampling was used by purposive sampling technique, resulting in 109 respondents. By using SPSS software. The results of this study are that Entertainment, Interaction, Word of Mouth, and Trend have a positive influence on Consumer Purchase Behavior. Meanwhile, Customization has no influence or no negative effect on Consumer Purchase Behavior